PROFILE OF STUDENTS’ MATHEMATICAL LITERACY IN THE PYTHAGOREAN THEOREM BASED ON RASCH ANALYSIS - Sitompul, Linca Rotua Nian; Sainuddin, Syamsir; Junita, Ranisa (Numeracy, 2026)
This study aims to provide an overview of students’ mathematical literacy on the topic of the Pythagorean Theorem through a Rasch model analysis. The study focuses on identifying the level of difficulty of mathematical literacy indicators and mapping students’ abilities across these indicators. A quantitative descriptive approach with diagnostic analysis was employed. The participants consisted of twenty-two ninth-grade students from a junior secondary school in Jambi City selected through incidental sampling. The research instrument was a single open-ended problem developed based on seven mathematical literacy indicators referring to fundamental mathematical capabilities. The data were analysed using the Rasch model by examining key outputs, including person summary, item difficulty, reliability, and the Wright map. The results indicate that students’ abilities are generally below the level of item difficulty and that the mapping of abilities has not yet shown sufficient stability. The variation in item difficulty shows that representation, the use of mathematical tools, and symbolic language are relatively easier, while communication, problem-solving strategies, and reasoning tend to be more difficult. These findings indicate a difference between students’ abilities and the demands of the indicators, particularly in modelling, explanation, and reasoning.